From village to city : social transformation in a Chinese county seat - Kipnis, Andrew B. (University of California Press, 2016)
"Between 1988 and 2013, the Chinese city of Zouping transformed from an impoverished village of 30,000 people to a bustling city of over 300,000, complete with factories, high rises, parks, shopping malls, and all the infrastructure of a wealthy East Asian city. From Village to City paints a vivid portrait of the rapid change of Zouping, its environs, and the lives of the once-rural people who live there. Despite its modernization and higher standards of living, Zouping is far from a utopia; its inhabitants face new challenges and problems such as alienation, class formation and exclusion, patriarchy, and pollution. To understand this transformation, Andrew B. Kipnis has developed a theory of urbanization, demonstrated in his compelling portrayal of an emerging metropolis and the hopes, fears, joys, and sorrows of the people who call it home"--Provided by publisher